A study on Long-term orientation, Self-Efficacy and Self-derogation of Kudumbashree members with special reference to Self Help Group in Kerala - Salim, Ms.Ansa; Sulphy, Dr MM (International Journal of Scientific Research and Management (IJSRM), 2015)
In the amount of post Indian Independence, the govt. developed the community development programmers specializing in socio-economic and political management of the folks. Without considering the psychological management of the mass a development programmer cannot accomplish its full potential. Self-efficacy is associate degree inevitable consider psychological empowerment, and at identical time self-derogation can have an effect on psychological management negatively. During this study these 2 variables accustomed live the impact of Kudumbashree project “Poverty demolition Mission” below Kerala Government in its members. The study revealed that the Kudumbashree members have higher self-efficacy and fewer self-derogations than the non beneficiaries of Kudumbashree. There’s correlation statistics between self-efficacy and self-derogation